All-Solid-State Lithium-Sulfur Battery Based on a Nanoconfined LiBH4 Electrolyte. Issue 9 (1st January 2016) - Das, Supti; Ngene, Peter; Norby, Poul; Vegge, Tejs; de Jongh, Petra E.; Blanchard, Didier
Abstract : In this work we characterize all-solid-state lithium-sulfur batteries based on nano-confined LiBH4 in mesoporous silica as solid electrolytes. The nano-confined LiBH4 has fast ionic lithium conductivity at room temperature, 0.1 mScm −1, negligible electronic conductivity and its cationic transport number (t+ = 0.96), close to unity, demonstrates a purely cationic conductor. The electrolyte has an excellent stability against lithium metal. The behavior of the batteries is studied by cyclic voltammetry and repeated charge/discharge cycles in galvanostatic conditions. The batteries show very good performance, delivering high capacities versus sulfur mass, typically 1220 mAhg −1 after 40 cycles at moderate temperature (55°C), 0.03 C rates and working voltage of 2 V.